Utilization of Green Tea Extract and Pineapple in Jelly Candy - Rizki Azhari; Noviar Harun; Dewi Fortuna Ayu (JURNAL AGROINDUSTRI HALAL, 2021)
The ratio of green tea extract and pineapple juice on the quality and sensory properties of the jelly candy was studied. This research used a Complete Randomized Design with five treatments and three replications followed by Duncan's New Multiple Range Test at a 5% level. The treatment in this research was the ratio of green tea extract and pineapple juice included NT1 (1: 99), NT2 (2: 98), NT3 (3: 97), NT4 (4: 96), and NT5 (5: 95). The analysis showed that the ratio of green tea extract and pineapple juice significantly affected moisture content, ash content, pH, reduction sugar content, antioxidant activity, colour, flavour, taste, and overall assessment but did not significantly affect the elasticity of jelly candy. The best formulation of jelly candy was NT1 with 21.65% water, 1.91% ash, 4.77pH, 4.80% sugar reduction, and 101.49ppm antioxidants activity. NT1 organoleptic score with descriptions of yellow, pineapple-flavoured, pineapple flavour, and chewy texture. The panellists also favoured the overall hedonic assessment of the NT1 treatment jelly candy with a score of 3,83.